HAZOP analysis‐based dynamic simulation and its application in chemical processes. Issue 6 (24th August 2015) - Tian, Wende; Du, Tingzhao; Mu, Shanjun
Abstract: Hazard and operability analysis (HAZOP) is widely applied in petroleum industry as a scientific and effective safety analysis method, but it is traditionally qualitative in essence and hereby has such shortages as vague conclusions, susceptible to human factor, lack of comprehensive consideration, and so on. This paper proposed a dynamic simulation‐based quantitative HAZOP method that utilizes dynamic simulation to reason deviations to reduce uncertainty in manual analysis. It transforms deviations into quantitative dynamic tasks and uses these tasks to activate dynamic simulation for quantitative deviation reasoning work. The possible consequence and propagation time caused by deviation is probed by analyzing simulation results. In this process, some deviations that appeared seldom or did not at all before can also be simulated and analyzed with the aid of dynamic mechanism model. Case studies in extractive distillation and ammonia synthesis loop showed that this method can present propagation effect of key process parameters on safety state and is useful for iterative and automatic assessment work. It is also found that detailed operation and device data are necessary for initial complex process modeling. In addition, we should improve simulation platform to meet practical requirements when applying this method. © 2015 Curtin University of Technology and John Wiley & Sons, Ltd.